The awareness towards the importance of health waqf in Malaysia / Abg Akmal Azani Izzat Abg Marzuki ... [et al.] - Abg Marzuki, Abg Akmal Azani Izzat; Mohammad Amin, Syaheerah Atiqah; Haroming, Nurul Anissa; Sultan Mohideen, Rosilawati; Ilyas, Ilya Yasnoriza (Faculty of Communication & Media Studies, 2021)
Health Waqf is a term used to define a perpetual dedication of any property from which its benefit is used for health facilities purposes. The aim of this study is to identify the level of awareness towards the importance of Health Waqf among Malaysian people. An online questionnaire with 11 items at demographic section and 14 items was designed to evaluate the aspect of Health Waqf. This study involved 411 respondents which are from all over the country by using Google Form Platform. The amount of survey calculated based on Raosoft Calculator, N=33.45 million, S=385.All variables were measured through scales previously used by other researchers. SPSSS ver. 20 software was used in the analysis and the results of the SPSS indicated that the level of awareness regarding Health Waqaf is high (M=2.61). Besides, it can be concluded that people are well aware of the importance of Health Waqf (M=3.53).